Biosci. J. 2017
DOI: 10.14393/bj-v33n1a2017-34483
|View full text |Cite
|
Sign up to set email alerts
|

Early treatment of nonsyndromic oligodontia: a clinical case report

Abstract: ABSTRACT:This report aims to describe the clinical case of a 10-year-old male patient (R.C.B.C.), presenting nonsyndromic oligodontia with maternal family trait and absence of 22 permanent teeth. Clinically, the patient had prolonged retention of some primary teeth and presence of permanent maxillary left central incisor, permanent mandibular right central incisor and four first permanent molars. Radiographically, only permanent maxillary second molars and mandibular third molars were developing, whereas all o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
1
0
0
Order By: Relevance
“…Thus, the groups that ate the feeds with higher DC contents showed lower weight gains. The same result is reported in another investigation [34], which reports the effects of different proportions of Brazil nuts in a diet based on rice and beans. The authors concluded that the animals that ate higher amounts of nuts had lower weight gain and the animals that ate the ideal amount of DC had optimal growth.…”
Section: Resultssupporting
confidence: 85%
“…Thus, the groups that ate the feeds with higher DC contents showed lower weight gains. The same result is reported in another investigation [34], which reports the effects of different proportions of Brazil nuts in a diet based on rice and beans. The authors concluded that the animals that ate higher amounts of nuts had lower weight gain and the animals that ate the ideal amount of DC had optimal growth.…”
Section: Resultssupporting
confidence: 85%